STUDI LITERATUR EFEKTIVITAS PENGGUNAAN VIRTUAL LABORATORY DALAM PEMBELAJARAN KIMIA SECARA LURING - Darojat, Alfiyah (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
This study aims to determine the effectiveness of the use of virtual laboratories in chemistry lessons. Chemistry is a lesson that is very close to practicum activities, but it is feared that the use of chemicals in the practicum will pollute the environment, so a virtual lab was developed. Research activities are carried out using the literacy study method, namely by combining 6 journals. The results obtained from this literature study are chemistry learning carried out with a practicum using a virtual laboratory to provide a sense of comfort to students during the practicum so that students can more easily understand the material and have a deeper impression